A demonstration of nesting in two antarctic icefish (genus Chionodraco) using a fin dimorphism analysis and ex situ videos. - Sara Ferrando; Laura Castellano; Lorenzo Gallus; Laura Ghigliotti; Maria Angela Masini; Eva Pisano; Marino Vacchi (PLoS ONE)
Visual observations and videos of Chionodraco hamatus icefish at the "Acquario di Genova" and histological analyses of congeneric species C. hamatus and C. rastrospinosus adults sampled in the field provided new anatomical and behavioral information on the reproductive biology of these white blooded species that are endemic to the High-Antarctic region. During the reproductive season, mature males of both species, which are different from females and immature males, display fleshy, club-like knob modifications of their anal fin that consisted of a much thicker epithelium. Histology indicated that the knobs were without any specialized glandular or sensorial organization, thus suggesting a mechanical and/or ornamental role of the modified anal fin. In addition, the occurrence of necrotic regions at the base of the thickened epithelium and the detachment of the knobs in post-spawning C. hamatus males indicated the temporary nature of the knobs. The role of these structures was confirmed as mechanical and was clarified using visual observations and videos of the behavior of two C. hamatus during a reproductive event that occurred in an exhibit tank at the "Acquario di Genova". The reproductive process included pre-spawning activity, preparation of the nest, egg guarding and successfully ended with egg hatching. When the spawning event approached, the male prepared the nest. The nest was constructed on an accurately selected bottom surface, which was flattened and maintained free from sand or debris by a combination of radial body movements and continuous anal fin sweeping, thus demonstrating the important mechanical/abrasive function of the anal fin knobs. The present data are the first records of active nesting in icefish and clarify the meaning of dimorphic temporary structures, whose function would have been difficult to obtain in the field.